Impact of Financial Literacy on Financial Behavior and Entrepreneurial Intention: Gender as a Moderator. Study on Undergraduate Students in Kupang City - Maria Maria (Institute of Computer Science (IOCS), 2022)
This study aims to investigate the moderating role of gender in the relationship between financial literacy and financial behavior, as well as the relationship between financial literacy and entrepreneurial intention. Data were obtained from 164 final year students who voluntarily acted as respondents. With a quantitative approach, the data that has been obtained is then analyzed using the Structural Equation Modeling (SEM) technique with the help of SmartPLS 3.0 software. The results of this study indicate that gender differences among students moderate the relationship between financial literacy and financial behavior, as well as the relationship between financial literacy and entrepreneurial interest. In addition to theoretical contributions, practical contributions from this research can be applied by stakeholders to foster intention to be entrepreneurs among students.